Impaired excitability of renal afferent innervation after exposure to the inflammatory chemokine CXCL1 - Ditting, Tilmann; Freisinger, Wolfgang; Rodionova, Kristina; Schatz, Johannes; Lale, Nena; Heinlein, Sonja; Linz, Peter; Ott, Christian; Schmieder, Roland; Scrogin, Karie E.; Veelken, Roland (American Journal of Physiology-Renal Physiology, 2016)
Recently, we showed that renal afferent neurons exhibit a unique firing pattern, i.e., predominantly sustained firing, upon stimulation. Pathological conditions such as renal inflammation likely alter excitability of renal afferent neurons. Here, we tested whether the proinflammatory chemokine CXCL1 alters the firing pattern of renal afferent neurons. Rat dorsal root ganglion neurons (Th11-L2), retrogradely labeled with dicarbocyanine dye, were incubated with CXCL1 (20 h) or vehicle before patch-clamp recording. The firing pattern of neurons was characterized as tonic, i.e., sustained action potential (AP) firing, or phasic, i.e., <5 APs following current injection. Of the labeled renal afferents treated with vehicle, 58.9% exhibited a tonic firing pattern vs. 7.8%, in unlabeled, nonrenal neurons (P < 0.05). However, after exposure to CXCL1, significantly more phasic neurons were found among labeled renal neurons; hence the occurrence of tonic neurons with sustained firing upon electrical stimulation decreased (35.6 vs. 58.9%, P < 0.05). The firing frequency among tonic neurons was not statistically different between control and CXCL1-treated neurons. However, the lower firing frequency of phasic neurons was even further decreased with CXCL1 exposure [control: 1 AP/600 ms (1-2) vs. CXCL1: 1 AP/600 ms (1-1); P < 0.05; median (25th-75th percentile)]. Hence, CXCL1 shifted the firing pattern of renal afferents from a predominantly tonic to a more phasic firing pattern, suggesting that CXCL1 reduced the sensitivity of renal afferent units upon stimulation.
EVALuna2:3740

Influence of fractional Radio(chemo)therapy on the Expression Patterns of immunocheckpoint Molecules on Glioblastoma Cell Lines - Ladinig, A.; Schatz, Johannes; Fischer, R.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Derer, Anja (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02